Space layout and energy performance: Parametric optimisation of space layout for the energy performance of office buildings - Du, Tiantian (A+BE | Architecture and the Built Environment, 2021)
Studies have shown that space layout design can impact the building energy performance (BEP). However, its isolated effect on the BEP has not been identified yet. Performative computational architecture has proven to be effective to improve the BEP. However, only a few studies have tried to apply the performative computational architecture to space layout design. This research aims to investigate how space layout affects BEP, and to develop a computational optimisation method for space layout to improve the BEP of office buildings. Firstly, the mechanism on how space layout affects the BEP and how much energy is affected by space layout were identified through literature review and simulation. 11 layouts with different function allocations were simulated and compared. The outcome showed that layout variance affected lighting the most, and the maximum difference happened in Harbin, being 46% without shading and 35% with shading. As a follow-up, another literature review was conducted, which identified the functional requirements of space layout design, methods for automatic generation of space layout, and requirements for energy performance optimisation. In addition, a computational method was developed to optimise space layout design for energy performance improvement, regardless of functional requirements. As a result, the relationship between space layout and energy demands were recognised. In conclusion, space layout has proven to be a significant influence on the BEP, and conscientious design can improve it. For optimal energy performance, manual design of space layout is not feasible; in order to do that, a computational approach is needed.